Measuring the Contribution of Livestock to Household Livelihoods : A Livestock Module for Multi-topic Household Surveys - Pica-Ciamarra, Ugo; Baker, Derek; Morgan, Nancy; Zezza, Alberto (World Bank, Washington, DC, 2014)
About 60 percent of rural households in developing countries are estimated to fully or partly depend on livestock for their livelihoods. Available household level livestock data, however, are insufficient to appreciate the contribution of livestock to household livelihoods, including both the monetary and non-monetary benefits provided by farm animals. This challenges the design and implementation of effective investments in the sector. This paper presents a livestock module for multi-topic household surveys, which targets improved livestock-related questions therein. The livestock module for multi-topic household surveys has been jointly elaborated by the FAO, the ILRI (International Livestock Research Institute) and the World Bank, as part of the Livestock Data for Better Policies in Africa Project. It consists of a core set of questions, which quantify both livestock herd and the various contributions of farm animals to household livelihoods, including cash income, food, manure, draft power and hauling services, savings and insurance and social capital. It then includes additional detailed questions on livestock characteristics (e.g. breeding, branding, etc.), husbandry practices (e.g. feeding, watering, etc.) and outputs (e.g. milk, dung, etc.) which, depending on the country, may or may not be included in multi-topic household surveys. The module is a public good, which has been used to develop multi-topic household questionnaires in collaboration with country governments in Niger, Tanzania and Uganda. Data from these surveys will be freely available for analysis in 2012 and 2013, providing an unprecedented opportunity to enhance the understanding of the livestock poverty-wellbeing linkages at the household level.